Prices and investment with collateral and default - Michael Magill; Martine Quinzii (University of California, Department of Economics, 2014)
This paper uses the framework of an OLG economy with three-period lived agents in which a durable good serves as collateral for loans, to study the effect of an unanticipated income shock when the economy is in a steady state equilibrium. We focus on the consequence of default on loans when the value of the collateral falls below the value of the debt it secures. We analyze the impulse response functions of the price and production of the durable good and show that there is an asymmetry between the response of the price and investment of the durable good to a positive and a negative income shock arising from default on the collateralized loans.
Keywords: 330